Prevalência e fatores associados aos fenótipos de sibilância recorrente do programa de asma de Nova Lima - MG - Rosilea Alves da Silva (2011)
Objective: To review the literature about the incidence, prevalence and the factors associated to recurrent wheezing phenotypes in childhood evaluating its contribution for understanding the causal mechanisms, prognosis and wheeze therapeutics. Data source: non-systematic literature review, referring to the late 27 year period, using the PubMed/ MEDLINE/LILACS/IBEC and Adolec data basis, from the descriptors as follows: breath sounds, phenotypes, immediate hypersensitivity, asthma, risk factors. Data synthesis: The phenotype classifications of recurrent wheezing in childhood, in most revised studies, were based on predictive factors in the different age groups, resulting in three phenotypes, namely: early transient, persistent early onset and late onset wheeze. Other patterns were named intermittent wheeze, prolonged early wheeze, and intermediate onset wheeze, episodic viral and multiple-trigger wheeze. Transient wheeze incidence varied between 9,9% to 50,6%. For persistent wheeze early onset and late onset the incidences varied from 6,4% to 30% and 3,3 to 19,4%, respectively. Transient wheeze prevalence varied from 7,5 to 9%. Pre and perinatal conditions were associated to the early stop wheezing phenotypes. Atopy and environmental influences during breast feeding were associated to persistent and late onset wheezing. Conclusions: the phenotypes associated factors depend on the genetic and environmental interactions and on the age in which they occur. There is great variance in the phenotypes incidence and prevalence due to the differences in the employed methodology. The phenotypes can overlap and further studies are needed, with standardized methodology, so as to assess the applicability of these phenotypic expressions in several clinical settings.